La ferrovia da Napoli per Nocera e Castellammare le città vesuviane nel primo paesaggio ferroviario italiano (1839-1860) - Valeria Pagnini (UrbsHistoriaeImago: Storia e immagine dei territori, dei centri urbani e delle architetture, 2019)
The railway from Naples to Nocera with a side branch to Castellammare, whose project was approved in 1836 and which was completed in 1844, represents the first and the most significant stage of the construction of the Bourbon railway infrastructure. The absolute novelty of the enterprise, a work of public utility entrusted in concession to the French engineer Armand Bayard de la Vingtrie, led to the development of new and pressing issues, which concern not only the physical dimension of the Vesuvian coast and its new structure, but also important matters of economy, law, administration, archaeological protection, as well as infrastructure and territory promotion issues. The volume, through the research and comparison of different archival and documentary sources, is intended to reread the history of the first Bourbon railway by bringing together the many aspects that characterized its design, construction and use up to the Unification of Italy. From this study emerges a perspective on the Vesuvian landscape and on its multiple and complex components, integrated in the new perception, intermittent and cursory, offered by the moving train.